LESSONS IN GRADE 10 MATHEMATICS FOR USE IN A FLIPPED CLASSROOM - Llona, Grace O.; Tonga, Daves L. (PEOPLE: International Journal of Social Sciences, 2020)
Low-performance, insufficient instruction time and difficulty in providing instructional needs for diverse learners are some of the prevalent problems in mathematics education. Flipped Classroom is a rising pedagogical model that exhibits promising features in battling these dilemmas. This study aimed to develop lessons that integrates flipped classroom, uses student collaboration and incorporates contexts from students’ culture and experiences. Mainly, this study provided ways on how teachers from rural areas with less technological accessibility, can implement this instructional model through the use of materials and platforms available in their community. The mixed method of research was used. Qualitative approach was utilized in the analysis of students’ responses in their interviews and journals and the quantitative approach was done through pre-experimental design. Interviews to teachers and analysis of available data in the chosen school were done to know which topics are to be included in the study. The identified topics were examined to develop lessons that are best suited for the use of the model to Grade 10 Geometry. Ten lessons were made and implemented to a Grade 10 class to determine its effect on their task performance, conceptual understanding and problem-solving skills. Effects on study habits and interest were determined using interviews, journals and inventory. Results show that there is a significant difference on the performance of the students, within the considered constructs, before and after being exposed to flipped classroom. Moreover, positive change on responding to tasks, greater initiative to take part and higher interest levels were also revealed. The implementation of flipped classroom has deepen their understanding, positively affected the way they perceive and react to tasks, boost their interest and taught learners the accountability of their own learning. Additionally, availability of learning resources at home and support from knowledgeable others are important factors that help improve students’ performance.